Vertical 3D Nanostructures Boost Efficient Hydrogen Production Coupled with Glycerol Oxidation Under Alkaline Conditions - Li, Shanlin; Liu, Danmin; Wang, Guowei; Ma, Peijie; Wang, Xunlu; Wang, Jiacheng; Ma, Ruguang (Nano-Micro Letters, 2023)
Hydrogen production from electrolytic water is an important sustainable technology to realize renewable energy conversion and carbon neutrality. However, it is limited by the high overpotential of oxygen evolution reaction (OER) at the anode. To reduce the operating voltage of electrolyzer, herein thermodynamically favorable glycerol oxidation reaction (GOR) is proposed to replace the OER. Moreover, vertical NiO flakes and NiMoNH nanopillars are developed to boost the reaction kinetics of anodic GOR and cathodic hydrogen evolution, respectively. Meanwhile, excluding the explosion risk of mixed H2/O2, a cheap organic membrane is used to replace the expensive anion exchange membrane in the electrolyzer. Impressively, the electrolyzer delivers a remarkable reduction of operation voltage by 280 mV, and exhibits good long-term stability. This work provides a new paradigm of hydrogen production with low cost and good feasibility. Highlights: 1 Two types of vertical 3D nanostructures were successfully fabricated using simple hydrothermal and heat treatment processes for hydrogen evolution reaction and glycerol oxidation reaction (GOR). 2 Hydrogen production at a lower potential was achieved by replacing oxygen evolution reaction with GOR, reducing the device potential by approximately 300 mV. Additionally, organic membranes were used as separators, avoiding the use of expensive anion exchange membranes.